Pembentukan 8-OHdG dari Zat Toksik Pemicu Radikal Bebas - Dani, Intan Cahaya; Budiawan, Budiawan (Pharmaceutical Sciences and Research, 2015)
This study was conducted to observe the profile of DNA Adduct (8-OHdG) formation as DNA damage indicators, by using calf thymus DNA incubated with toxic and carcinogenic compounds. The compounds which could trigger free radicals in this research were PAH(Benzo[a]Pyrene), TiO2, and CuCl2. Calf thymus DNA was incubated with Benzo[a]Pyrene and CuCl2 compounds under pH and temperature variations. The incubation of calf thymus DNA with TiO2-UV radiation (254 nm) was used to induce the formation of reactive oxygen species (ROS) in the process of oxidative DNA damage. From this research, all of compounds have potency to trigger the formation of DNA Adduct (8-OHdG). The ratio of absorbance to assess the purity of DNA at 260 nm and 280 nm (λ260/ λ280 ) was measured at ~1.9. The shifted peaks at λmax were indicating changes on structures of DNA as a result of calf thymus DNA incubation with B[a]P and CuCl2. The highest level of 8-OHdG results in calf thymus DNA incubation with B[a]P and CuCl2 under pH 8.5 and incubation temperature at 60°C, was about 120.856 μg/L. Calf thymus DNA incubation with TiO2-UV radiation (254 nm) under pH 8.5 resulting 8-OHdG level at 57.025 μg/L.